Residents` perceptions of mega sport event legacies and impacts - Scheu, A.; Preuss, H. (German Journal of Exercise and Sport Research, 2018)
The purpose of this study was to examine perceptions of local residents prior to the public referendum for the 2024 Hamburg Olympic bid and to assess their level of support for the bid. The representative survey conducted amongst Hamburg residents reveals a high level of support but also a strong perception of negative legacies. A comparison between the perceived positive and negative legacies shows that the negative legacies outweigh the positive legacies. When examining factors that influence support, statistical analysis reveals the perception of positive legacies as the strongest predictor of support. The survey also indicates that residents attach great importance to the costs of the Games and feel no personal benefit from hosting them. The findings suggest that Games organizers and authorities should mostly rely on positive legacies while negative legacies ought to be mitigated.